Extract of Calotropis gigantea Leaves to Repair the Histological Profile of Fibrosarcoma Mice (Mus musculus) - Muchtaromah, Bayyinatul; ., Muchtaromah; Mutiah, Roihatul; Aprinda Kristanti, Mutiah; Ahmad, Mujahidin (International Journal of Engineering and Technology, 2019)
Calotropis gigantea (C. gigantea) is widely known as a traditional medicine for diseases such as toothache, colds, asthma. It also used be as a detoxifying agent and an anticancer drug. The leaves contain cardenolide, a bioactive agent which has cytotoxic properties against cancer cells, particularly fibrosarcoma. The active ingredient is able to control the mitochondria (the energy-producing cell organelle) essential for the growth of cancer cells. This study aimed to determine the effect of ethanol extract of C. gigantea leaves on the histological profile of fibrosarcoma mice (Mus musculus). The mice was induced with 7,12-Dimethylbenz [a] anthracene (DMBA) 25 mg/kg bw twice for 6 weeks, then treated by extract of C. gigantea leaves for 2 weeks. This experimental study employed a completely randomized design (CRD) with 6 treatments and 5 replications. The treatments consisted of negative control (C-), positive control (C+), dose of 50 mg/kg bw (T1), dose of 100 mg/kg bw (T2), dose of 150 mg/kg bw (T3), methotrexate dose of 2.5 mg/kg bw (T4). The study observed 30 male mice aged 50-60 days. The data consisted of the number of fibroblasts and the level of collagen fiber damage in skin tissue. The data were analyzed by one way ANOVA, followed by DMRT 1 %. The results showed that the extract of C. gigantea leaves repaired the histological profile of fibrosarcoma mice significantly, indicated by the decreasing of fibroblast proliferation and repairing of collagen fibers in mice skin tissue. The extract of C. gigantea leaves at a dose of 150 mg/kg bw (T3) gave a better effect to repair the histological profile of fibrosarcoma mice than the cancer drug methotrexate synthesis dose of 2.5 mg/kg bw (T4) and other treatments.Â